Islamic Economics and Social Justice: Zakat, Waqf, and Poverty Alleviation - Layyinatus Shifah; Sugianto Sugianto; Siti Mutmainah; lham Akbar; Deo Renaldi Saputra (Indonesian Journal of Sharia and Islamic Sciences, 2026)
Islamic economics emphasizes social justice as a core objective, positioning zakat and waqf as fundamental instruments for poverty alleviation and equitable wealth distribution. This article examines the role of zakat and waqf within contemporary Islamic economic frameworks, focusing on their capacity to address both immediate poverty and structural inequality. Through a qualitative analysis of recent scholarly literature, the study highlights how zakat functions as a redistributive mechanism that reduces income disparities and social vulnerability, while waqf contributes to long-term economic empowerment by supporting education, health services, and productive economic activities. The findings indicate that an integrated approach to zakat and waqf management enhances financial inclusion, institutional effectiveness, and sustainability of poverty reduction programs. Furthermore, the study underscores the importance of governance, digital innovation, and policy alignment in maximizing the social impact of Islamic social finance. By combining ethical principles with institutional innovation, Islamic economics offers a comprehensive model for achieving social justice and sustainable development in Muslim societies.